2012
DOI: 10.1080/10615806.2011.605879
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms in native and immigrant adolescents: the role of critical life events and daily hassles

Abstract: The present study compared native Austrian, first and second generation immigrant adolescents regarding their level of depressive symptoms, critical live events, and daily hassles. Furthermore, the associations between these constructs were tested in the three groups. The sample comprised 330 native Austrian (52.1% girls), 120 first generation immigrants (49.2% girls and 159 second generation immigrants (54.2% girls) aged 14-19 (M=15.61). Compared with native adolescents, first generation immigrant adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 46 publications
2
45
0
1
Order By: Relevance
“…The MASSQ questionnaire mainly consists of a 25-item disability/symptom scale regarding andropause that was investigated by authors and literature reviews. [24712192123262834] Each item in the disability/symptom scale has five response options from 1 = none to 5 = extremely severe. If the 25 items are completed, a scale score ranging from 25 (no symptoms) to 125 (most severe symptoms) can be calculated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MASSQ questionnaire mainly consists of a 25-item disability/symptom scale regarding andropause that was investigated by authors and literature reviews. [24712192123262834] Each item in the disability/symptom scale has five response options from 1 = none to 5 = extremely severe. If the 25 items are completed, a scale score ranging from 25 (no symptoms) to 125 (most severe symptoms) can be calculated.…”
Section: Methodsmentioning
confidence: 99%
“…[241112] Attaining knowledge regarding andropause will help the caregivers and gerontologists to achieve the ultimate goal of a dignified healthy ageing[131415] and maintain the highest quality of life. [21617181920] Thus, it's adding life to years and not simply years to life[20212223242526272830] While ignorance about andropause persists, having an instrument turns out to be a necessity. [923242526] It's helpful even in the clinical treatment as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nguyen et al, 2011;Stefanek et al, 2012;Van Voorhees et al, 2008;Ying & Han, 2008). Underresearched is how these factors may differ for immigrant and native adolescents.…”
Section: Risk and Protective Factors Of Depressionmentioning
confidence: 99%
“…Stress is heightened in adolescents and immigrants. A study in 600 healthy adolescent boys and girls in Austria reported more depressive symptoms and more daily hassles in first and second‐generation immigrants than native Austrians (Stefanek, Strohmeier, Fandrem, & Spiel, ). The hassles in these teens were related to interpersonal relationships, schooling, and leisure.…”
Section: Introductionmentioning
confidence: 99%